NATIONAL INFORMATION COMMUNICATION TECHNOLOGY POLICY AND TEACHING QUALITY IN NIGERIAN UNIVERSITIES - Ugo Chuks Okolie (Universitas Pendidikan Indonesia (UPI), 2023)
This study examines national information communication technology policy and its impact on teaching quality in Nigerian universities. This study adopted qualitative research design as it relies on secondary data collected from books, journal articles and internet sources, and were content analyzed in relation to the scope of the study. This study is anchored on Technology Organization Environment model which offers analytical explanations on information communication technology policy implementation and teaching quality in higher educational institutions. The study concludes that the integration of information communication technology into educational system has been identified as a critical catalyst to achieving quality of teaching and learning across the globe, and since academic quality is the primary objective of Nigerian universities and has been pursued traditionally for decades, it thus becomes important to source for role or outcome specific technologies that can be used to substitute or improve the traditional teaching practices. This study therefore recommends among others that Nigeria government should intensify effort to invest more on information communication technology infrastructures aimed at improving teaching quality in Nigerian universities.